Graphitic phosphorus coordinated single Fe atoms for hydrogenative transformations - Xiangdong Long (Nature Portfolio, 2020)
Phosphorus ligands have been extensively used in metal complexes for homogeneous catalysis. Here, the authors broaden this scope to heterogeneous catalysis by preparing a P-coordinated Fe single atom catalyst with excellent catalytic performance in hydrogenative transformations.